The Effect of Environmental Performance, Intellectual Capital, Institutional Ownership on Corporate Profitability with Corporate Social Responsibility as a Moderating Variable - Alberta Rene; Florida Mini; Ancelia Kartika Ji’e (Journal of Applied Accounting and Sustainable Finance, 2026)
Purpose – This study aims to obtain empirical evidence on the influence of environmental performance, intellectual capital, and institutional ownership, on Corporate profitability. Design/methodology/approach – This study employs a quantitative research method using secondary data. The population consists of 73 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sample comprises 34 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the same period. The total number of observations in this study is 102. The hypothesis testing is conducted using multiple regression analysis with E-Views 9 software. Findings – The results of this study indicate that the environmental performance variable has a positive and significant effect on firm profitability. The intellectual capital variable has a negative and insignificant effect on firm profitability. The institutional environment has a positive and significant effect on firm profitability. Research limitations/implications – This study aims to provide information on firm profitability provides an overview of a company’s ability to generate profits efficiently.   JEL : 14, M41, G34, O34, L25